The impact of Educational Initiatives on Identifying Youth Entrepreneurial Talents in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Within the context of India's youth population, the purpose of this study is to evaluate theimpact that educational programmes have on the discovery and development of innovative andentrepreneurial skills. In light of the fast shifting economic landscape and the growing significance ofentrepreneurship in promoting innovation and economic growth, it is of the utmost importance to have aknowledge of the ways in which educational programmes assist to the identification and development ofentrepreneurial potential. For the purpose of gathering thorough data, the research makes use of amixed-methods technique, which combines qualitative interviews and quantitative surveys. The researchfocuses on a variety of educational initiatives that have been adopted across a range of educationallevels. These efforts include mentoring programmes, extracurricular activities, and entrepreneurshipclasses. A representative sample of students from secondary schools, colleges, and universities locatedall throughout India will be surveyed as part of the quantitative phase of the research. The purpose ofthis survey is to evaluate the influence that particular educational interventions have had on students'knowledge of entrepreneurship, the development of their mindsets around entrepreneurship, and theidentification of their own potential to be entrepreneurial. In-depth interviews with educators, industryprofessionals, and successful business owners are conducted during the qualitative phase of theresearch project. The purpose of these interviews is to acquire insights on the efficacy of variousteaching methodologies. Additionally, case studies of successful entrepreneurial firms that originatedfrom educational efforts will be analysed in order to identify trends and most important variables thatcontributed to their success.